Rock art in the Swat Valley, Pakistan - Badshah Sardar (Ancient Asia, 2012)
Swat valley, an administrative district of the province of Pakistan is rich in innumerable ancient remains like stupas, monasteries, viharas, forts, castles, petroglyphs, carvings, rock inscriptions, painted shelters and stele. This paper attempts to study the rock art of the region including the published materials as well as the author’s new discoveries. ' '